2022
DOI: 10.3390/ijms23137089
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Specific gp130 Signalling Underlies APAP Induced Liver Injury

Abstract: N-acetyl-p-aminophenol (APAP)-induced liver damage is associated with upregulation of Interleukin-11 (IL11), which is thought to stimulate IL6ST (gp130)-mediated STAT3 activity in hepatocytes, as a compensatory response. However, recent studies have found IL11/IL11RA/gp130 signaling to be hepatotoxic. To investigate further the role of IL11 and gp130 in APAP liver injury, we generated two new mouse strains with conditional knockout (CKO) of either Il11 (CKOIl11) or gp130 (CKOgp130) in adult hepatocytes. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This, in conjunction with glutathione depletion and accumulation of the toxic metabolite NAPQI, could result in immediate acute liver injury. This is a particularly interesting result given that for many years, the pg130 pathway and Il11 were both considered to have a protective role in mouse models of liver injury; in line with more recent articles [ 5 ], the authors showed that aggregate gp130 signaling and Il11 upregulation in a damaged liver are toxic and antiregenerative after APAP treatment [ 3 ].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…This, in conjunction with glutathione depletion and accumulation of the toxic metabolite NAPQI, could result in immediate acute liver injury. This is a particularly interesting result given that for many years, the pg130 pathway and Il11 were both considered to have a protective role in mouse models of liver injury; in line with more recent articles [ 5 ], the authors showed that aggregate gp130 signaling and Il11 upregulation in a damaged liver are toxic and antiregenerative after APAP treatment [ 3 ].…”
supporting
confidence: 53%
“…Its toxicity, whether via accidental or intentional overdose, is an ongoing global problem that continues to result in severe cases of hepatotoxicity, acute liver failure, and even irreversible liver injury necessitating liver transplantation. While many studies have confirmed that hepatotoxicity from paracetamol overdose is mainly due to glutathione depletion and the subsequent accumulation of harmful metabolites, new studies, including those by Dong [ 3 ] and Gajdošik [ 4 ] published in this issue, also highlight the role played by other agents and signaling pathways in APAP-induced liver damage.…”
mentioning
confidence: 99%
“…A recent study demonstrated that activation of gp130 signaling can limit regeneration ( 47 ). Our data indicated that gp130 Y814 signaling may be a contributing factor (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of hepatocytes to IL11 causes cell death associated with activation of ERK, JNK and NOX4. In a mouse model of acetaminophen (APAP)-induced hepatotoxicity, hepatocyte-specific deletion of Il11ra1 , Il11 or gp130 promotes hepatocyte regeneration and liver repair [ 61 , 62 , 109 ]. Of note, hepatocyte regeneration is inhibited by SNAI1 expression [ 70 , 110 ].…”
Section: Cellular Pathobiology Of Il11mentioning
confidence: 99%
“…Perhaps the best example of this occurrence comes from liver studies: mice deleted for Il11ra1 were shown not to be protected from toxin-induced liver injury [ 35 ], which we replicated [ 61 ]. However, mice with hepatocyte-specific deletion of Il11ra1 [ 61 ], Il11 [ 62 ] or gp130 [ 109 ] are protected from this form of liver injury, as are mice administered either anti-IL11, anti-IL11R or siRNA against Il11 or Il11ra1 [ 61 , 95 , 96 ]. It is therefore likely that global germline deletion of Il11ra1 has secondary — direct or indirect — effects and insights derived using this strain should be validated with other approaches.…”
Section: Human and Mouse Genetics Of Il11 And Il11ramentioning
confidence: 99%